Оцінка навантаженості нелінійних з’єднань елементів системи турбоагрегат-фундамент-основа при сейсмічних діях - Гонтаровський, Павло Петрович; Гармаш, Наталія Григорівна (НТУ "ХПІ", 2018)
За допомогою розробленої на основі методу скінченних елементів розрахункової методики проведено аналіз навантаженості елементів кріплення турбоагрегату на фундаменті для різних варіантів їх пружно-демпферних характеристик. Розрахункова модель складалась із довільно орієнтованих стержнів та зосереджених мас. Оцінено навантаженість елементів упорного підшипника, який у більшості випадків має найменший запас міцності (несної здатності). Показано, що наявність зазорів у елементах кріплення викликає значне підвищення динамічних навантажень. Розрахунки проведено для синтезованої сейсмограми семибального землетрусу, яка викликає найбільш широкий спектр навантаження в порівнянні з іншими реальними сейсмограмами.

A loading of the fasteners of turbine unit on the foundation exposed to seismic activities was analyzed for different options of their elastically damped characteristics. The software and computation methods developed on the basis of the method of finite elements have been used. The calculation model of the dynamic turbounit-foundation-base system consisted of arbitrary oriented rods and concentrated masses that are rigidly interconnected or connected by linear and nonlinear elastically deformed elements. Rod finite elements with distributed parameters allow us to take into consideration all the types of deformations that take place at rod vibrations. The computation model allows us to take into consideration structural peculiarities of the system and also the peculiarities of its behavior at possible earthquakes. During the computations special attention was paid to the thrust bearing that in most cases has the lowest safe load factor (load-carrying capacity). It is shown that the availability of gaps in fastening elements results in a considerable increase of dynamic loads. Taking into account nonlinear strain characteristics of the oil layer of a thrust bearing results in an increase of the pressure on its shoes. The computations were done for the synthesized seismogram of a seven-point earthquake. Previous investigations showed that this seismogram results in the broadest loading spectrum in comparison to other real seismograms. The research data can be used for the design of high-power turbine units to determine their seismic stability.
Estimating the loading of nonlinear element connections in the unit-foundation-base turbine system at seismic activities
Keywords: сейсмічне навантаження; нелінійні пружно-демпферні елементи; атомна електростанція; АЕС; метод скінченних елементів; ТФО; циліндр високого тиску; ЦВТ; turbine unit; seismic loading